The role of macrophage polarization in tendon healing and therapeutic strategies: Insights from animal models - Yicheng Wang; Xiao Lu; Xiao Lu; Jianxi Lu; Jianxi Lu; Philippe Hernigou; Fangchun Jin (Frontiers in Bioengineering and Biotechnology, 2024)
Tendon injuries, a common musculoskeletal issue, usually result in adhesions to the surrounding tissue, that will impact functional recovery. Macrophages, particularly through their M1 and M2 polarizations, play a pivotal role in the inflammatory and healing phases of tendon repair. In this review, we explore the role of macrophage polarization in tendon healing, focusing on insights from animal models. The review delves into the complex interplay of macrophages in tendon pathology, detailing how various macrophage phenotypes contribute to both healing and adhesion formation. It also explores the potential of modulating macrophage activity to enhance tendon repair and minimize adhesions. With advancements in understanding macrophage behavior and the development of innovative biomaterials, this review highlights promising therapeutic strategies for tendon injuries.